Allergic contact dermatitis and periorbital oedema after permanent eyelash dye - Akdur Okhan; Akdur Gökhan; Bardakci Okan; Das Murat (Acta Marisiensis - Seria Medica)
Allergic contact dermatitis is a rare cause of emergency room visits. However, it can progress to life-threatening conditions such as urticaria and angioedema. In this report, we describe a case that developed severe allergic contact dermatitis around the eye applying an eyelash dye containing p-Phenylenediamine. A 21-year-old female patient was admitted to the emergency department with the complaint of swelling and redness around both eyes. Swelling and redness started 3 days ago with permanent eyelash dye (containing p-Phenylenediamine) application in the beauty center. Clinically, periocular edema and rash was suspected to be an allergic reaction to a substance contained in the eyelash dye. For allergic contact dermatitis, 40 mg methylprednisolone, 45.5 mg pheniramine maleate, IV bolus was administered. The vesicular rash was thought to be a herpes lesion. She was discharged from the emergency department, with an initial dose of 16 mg methyl prednisolone (discontinued by reducing the dose), 500 mg oral valacyclovir twice a day, mupirocin cream on twice a day and oral levocetrizine 5 mg once daily. It was observed that the patient’s lesions and redness regressed after 2 weeks. The effects of cosmetic products, which are the agents that come into contact with the skin most often, may differ individually. Agents included in cosmetic products, such as in our case, may cause severe contact dermatitis that requires treatment. Beauticians should also be informed about PPD. Patients who have had allergic reactions due to the use of PPD-containing dyes should use PPD-free cosmetic products.